Application of double-wall cooling structure in the integrated strut flame stabilizer. (1st December 2022) - Li, Wen; Tan, Xiaoming; Huang, Xiaofeng; Wei, Yuheng; Deng, Yuanhao
Highlights: After gas flows through the integrated strut, symmetrical spiral vortices and backflow vortices are formed behind the strut. Under the pressure of spiral vortices and backflow vortices, the cool air flowing out of the double-wall covers the wall surface to cool it. In the non-afterburner state, the cool air flowing out of the double-wall covers the wall in the form of film. In the afterburner state, the cool air flowing out of the double-wall covers the wall in the form of vortex film. With the increase of mass flow ratio, the cooling efficiency of double-wall increases, the film adhesion decreases, and the scale of the film vortex increases. Abstract: In this paper, the double-wall cooling structure is applied to the integrated strut flame stabilizer. The cooling performance and aerodynamic performance of the double-wall cooling structure under the non-afterburner state and afterburner state are studied through numerical simulation. The flow behind the strut and the interaction between the film outflow and the main flow are analyzed in detail. The effect of the mass flow ratio on the cooling performance of the double-wall is explored. The results show that the spiral vortexs and the backflow vortexs are the main components of the recirculation area behind the strut, and the flame burns stably in the recirculation area; under the pressure of the eddy current in the recirculation area, the cool air outflow covers the wall surface in the way of film or film vortex, which can effectively cool the wall surface; with the increase of mass flow ratio, the cooling efficiency of double-wall increases, the wall covering property of film decreases, and the scale of film vortex increases.